Age-induced changes in anti-tumor immunity alter the tumor immune infiltrate and impact response to immuno-oncology treatments - Sitnikova, Suzanne I.; Walker, Jennifer A.; Prickett, Laura B.; Morrow, Michelle; Valge-Archer, Viia E.; Robinson, Matthew J.; Wilkinson, Robert W.; Dovedi, Simon J. (Frontiers in Immunology, 2023)
Immuno-oncology (IO) research relies heavily on murine syngeneic tumor models. However, whilst the average age for a cancer diagnosis is 60 years or older, for practical purposes the majority of preclinical studies are conducted in young mice, despite the fact that ageing has been shown to have a significant impact on the immune response. Using aged (60-72 weeks old) mice bearing CT26 tumors, we investigated the impact of ageing on tumor growth as well as the immune composition of the tumor and peripheral lymphoid organs. We found many differences in the immune cell composition of both the tumor and tumor-draining lymph node between aged and young mice, such as a reduction in the naïve T cell population and a decreased intratumoral CD8/Treg ratio in aged animals. We hypothesised that these differences may contribute to impaired anti-cancer immune responses in aged mice and therefore assessed the anti-tumor efficacy of different IO therapies in aged mice, including both co-stimulation (using an anti-OX40 antibody) and immune checkpoint blockade (using anti-PD-L1 and anti-CTLA-4 antibodies). Whilst aged mice retained the capacity to generate anti-tumor immune responses, these were significantly attenuated when compared to the responses observed in young mice. These differences highlight the importance of age-related immunological changes in assessing and refining the translational insights gained from preclinical mouse models.